Decline of Collective Bargaining and Subsequent Developments in Labour Management Relations - Sridharan, Shashank (Christ University Law Journal, 2021)
Collective bargaining was a milestone in the labour-management relations in the context of welfare of labourers in the post-industrial revolution era. It was introduced to integrate the employers with the employees and to provide a common platform which could act as a grievance redressal mechanism. It instantly created a tremendous impact after being adopted as a part of ILO Declaration on Fundamental Principles and Rights at Work in 1998, and was binding on the member states. Despite the worldwide positive impact, collective bargaining began to lose its influence due to a plethora of social, economic and political changes. Opening up of economies due to phenomena like liberalization, privatization and globalization have resulted in a paradigm shift from centralized collective bargaining, to various forms of decentralized bargaining structures like unit, individual, commercial and collaborative bargaining. Market forces and heterogeneity in the workforce, due to immigration, part-time workers and impetus to gender equality, have placed an immense burden on the part of trade unions. This paper deals with the emergence and significance of the concept by examining the history of collective bargaining in India and its evolution, pre and post 1991. The paper specifically focuses on the reasons that led to the decline in collective bargaining. It also highlights the emerging trends as substitutes for collective bargaining in the labour-management relations, with their viability (along with the empirical data) and structure in the conclusion.